2017
DOI: 10.1002/mds.27232
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid, plasma, and saliva in the BioFIND study: Relationships among biomarkers and Parkinson's disease Features

Abstract: Objective: Examine relationships among neurodegenerative biomarkers and PD motor and nonmotor symptoms. Background: CSF alpha‐synuclein is decreased in PD versus healthy controls, but whether plasma and saliva alpha‐synuclein differentiate these groups is controversial. Correlations of alpha‐synuclein among biofluids (CSF, plasma, saliva) or biomarkers (eg, beta‐amyloid, tau [total, phosphorylated]) are not fully understood. The relationships of these biomarkers with PD clinical features remain unclear. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
120
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 37 publications
11
120
2
2
Order By: Relevance
“…[13][14][15] This is contrasted by the consistent finding that total α-synuclein protein levels are lower in CSF from PD patients compared to HCs at the population level, with significant overlap between the two groups. 17,28,29 Although the concordance rate was high between the two assays (92%; Fig. 1), we did not find any systematic explanation for the discrepant findings.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…[13][14][15] This is contrasted by the consistent finding that total α-synuclein protein levels are lower in CSF from PD patients compared to HCs at the population level, with significant overlap between the two groups. 17,28,29 Although the concordance rate was high between the two assays (92%; Fig. 1), we did not find any systematic explanation for the discrepant findings.…”
Section: Discussioncontrasting
confidence: 52%
“…Therefore, we undertook a blinded study of two similar assays that were separately developed by independent laboratories. These two platforms tested CSF from the same subjects in the BioFIND cohort, which utilized standardized biospecimen collection protocols of clinically typical and well‐defined moderate PD patients and healthy controls …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An initial study reported increased a-syn levels in plasma of PD patients compared with healthy controls (Lee et al 2006). However, subsequent reports found levels of total a-syn to be either increased (Duran et al 2010;Lin et al 2017), decreased (Li et al 2007), or not significantly different Foulds et al 2011;Mollenhauer et al 2011;Park et al 2011;Goldman et al 2018). Despite extensive efforts, results as to whether total a-syn concentrations in the blood differ between PD patients and healthy subjects yielded inconsistent findings.…”
Section: Measurement Of Different Forms Of A-syn In Biofluids and Permentioning
confidence: 99%
“…They identified greater increase of CSF αsynuclein levels after 1-year follow-up in patients with RBD compared to those without RBD. Meanwhile, in the Fox Investigation for New Discovery of Biomarkers in Parkinson's Disease (BioFIND), a cross-sectional and observational study assessing clinical features and CSF biomarkers of 115 moderate and advanced PD, CSF αsynuclein levels did not correlate with RBD questionnaire total score [49].…”
Section: Csf Biomarkers In Rbd α-Synucleinmentioning
confidence: 99%